TRANSFORMASI SIKAP MAHASISWA MENJADI GARDA TERDEPAN ANTI KORUPSI - Mubarok Mubarok; Diah Wulandari (LodDos Institute, 2023)
This research explores and analyzes the transformation of student attitudes as the vanguard in the anti-corruption movement. This phenomenon is the subject of research because of the key role of students in creating social change and building a society that is clean from corrupt practices. This research uses qualitative methods with in-depth interviews and content analysis of data related to student attitudes towards anti-corruption. The results showed a significant change in students' attitudes regarding anti-corruption, which included a deep understanding of the negative impacts of corruption, increased awareness of their role as agents of change, and an active commitment in fighting corruption. Factors such as education, participation in student organizations, and social interaction on campus have a great influence in shaping their attitudes. The transformation of student attitudes is not only limited to theoretical understanding, but also includes practical implementation through various initiatives, including anti-corruption campaigns, integrity training, and participation in policy reform advocacy. Students are perceived as frontline because of their role in voicing demands for transparency, accountability, and fairness. This research contributes to a further understanding of changing student attitudes in the context of anti-corruption, with important implications for the design of educational programs and anti-corruption advocacy in higher education environments. The transformation of students' attitudes is not only as a result of knowledge, but also as a tangible form of their active involvement in building a society free from corruption.